Option Investor Rationality Revisited: The Role of Exercise Boundary Violations. Issue 1 (24th January 2020) - Battalio, Robert; Figlewski, Stephen; Neal, Robert
Abstract : The authors dispute the theory that American call options should not be exercised early. By looking at intraday pricing, they find that the best bid price available is often lower than the option's intrinsic value and early exercise can be rational. Abstract : Our empirical results overturn the well-known textbook theory that American options should not be exercised early except in very limited conditions. In the real world, the best bid available in the market is frequently below the option's intrinsic value (e.g., nearly half of all quotes for in-the- money calls), which we call an "exercise boundary violation" (EBV). In an EBV, early exercise can be the right strategy and the "American" option characteristic has economic value. Some option holders do exercise, some sell at EBV bid prices, and our results suggest that actual exercise behavior is much less irrational than earlier studies concluded. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Notes Submitted 26 May 2019 Accepted 4 November 2019 by Stephen J. Brown. This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. Giuseppe Ballocchi, CFA, and William Fung were the reviewers for this article.